7‐Chloroquinoline–isatin Conjugates: Antimalarial, Antitubercular, and Cytotoxic Evaluation. (14th March 2014) - Raj, Raghu; Biot, Christophe; Carrère‐Kremer, Séverine; Kremer, Laurent; Guérardel, Yann; Gut, Jiri; Rosenthal, Philip J.; Forge, Delphine; Kumar, Vipan
<x xml:space="preserve">Abstract</x> A series of twenty piperazine‐tethered 7‐chloroquinoline–isatin hybrids have been synthesized via either direct nucleophilic substitution or Cu(Ι)Cl‐mediated Mannich reaction. These new conjugates were evaluated for their antimalarial and antitubercular efficacy against a chloroquine‐resistant strain of Plasmodium falciparum and Mycobacterium tuberculosis, respectively, while the cytotoxic profiles were evaluated against 3T6 cell line, a permanent mouse embryonic fibroblast cell line. The most potent of the test compound with IC50 of 0.22 μm against W2 strain of P. falciparum and 31.62 μm against the embryonic fibroblast cell line (cytotoxicity) displayed a high selective index of 143.73.